2018
DOI: 10.1080/09537287.2018.1448126
|View full text |Cite
|
Sign up to set email alerts
|

Modelling critical success factors for sustainability initiatives in supply chains in Indian context using Grey-DEMATEL

Abstract: Sustainability assists organisations to attain competitive edges through enhanced ecological, financial and societal performances of their entire supply chains. The adoption of sustainability is usually difficult for the organisations, especially in a developing nation, such as India due to the existence of various significant factors related to finance, management, government regulations etc. The present paper uncovers the Critical Success Factors (CSFs) for effective adoption of sustainability initiatives in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
91
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 150 publications
(94 citation statements)
references
References 118 publications
(139 reference statements)
1
91
0
2
Order By: Relevance
“…Similarly, policies from the governments and increased public awareness may create demands for achieving better environmental management. Thus, organizations and enterprises are often obliged to improve their green image by performing environmental practices [1]. In recent years, the industry and academia have increased interests in GSCM [2], and particularly in integration of supply chain and natural environmental concerns in GSCM.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, policies from the governments and increased public awareness may create demands for achieving better environmental management. Thus, organizations and enterprises are often obliged to improve their green image by performing environmental practices [1]. In recent years, the industry and academia have increased interests in GSCM [2], and particularly in integration of supply chain and natural environmental concerns in GSCM.…”
Section: Introductionmentioning
confidence: 99%
“…Among five experts, two are senior project managers; one academician; one forest ministry environmental representative; and one statistics implementation and climate change allied representative. Luthra et al (2018) used 5 experts in their research and suggested that more number of experts in Grey-DEMATEL may increase the data handling complexity. The individuals with on-job experience in the field of Energy Systems Management and Sustainability and Managing Environmental issues in Energy systems were considered.…”
Section: Data Analysis and Resultsmentioning
confidence: 99%
“…Step 4: Calculation of crisp relationship matrix (B): Modified-CFCS (Converting Fuzzy data into Crisp Scores) method is used to concert the grey number into crisp number (Please check supplementary file for more details of CFCS method). Further, the method had been explained by (Luthra et al, 2018) in their work.…”
Section: Literature Review Expert's Opinionmentioning
confidence: 99%
“…The key enabler concept is very helpful in process improvement in an organizational supply chain context (Rahman and Subramanian, 2012). This further helps in examining the role of people, functions and operations to enhance organization's brand image (Luthra et al, 2018). Thus, developing theory in area of sustainability oriented focused enablers linked to its recognition, need and significance is crucial in integrating sustainability initiative in food value chains.…”
Section: Implications To the Practice/managementmentioning
confidence: 99%
“…Understanding the contextual relationships between these enablers will help the manufacturers in effectively utilizing their resources and attaining sustainable initiatives in A-FSCs. A substantial amount of research has been focused on examining factors that are critical in implementing sustainable initiatives in supply chains from various perspectives (Ageron et al, 2012;Grimm et al, 2014;Raut et al, 2017;Luthra et al, 2018). To date, little attention has been devoted to enablers for effective adoption of sustainability initiatives in A-FSCs as a whole (from the system perspective).…”
Section: Introductionmentioning
confidence: 99%